(untitled) (Nexo Revista Científica, 2022)
The present investigation had the general objective of developing a cream-like liquor from the fruits of Syzygium cumini [L.] Skeels. For this, a hydroalcoholic extract was made from the pulp of the collected fruits and the Design Expert 11.0.1 software (Stad-Ease Inc., Minneapolis, USA) was used for the experimental design, the variables were the addition of extract (A%) and invert sugar syrup (B%). The number of combinations thrown by the program was 8 runs including 2 replicas. The extract obtained was characterized and the selected formulation was applied in two variants of traditional cocktails. The characterization of the extract obtained yielded a pH value where the anthocyanins present in it are stable, verifying the possible presence of pelargonidin, cyanidin, delphinidin, peonidin, petunidin and malvinidin. The total polyphenol content was 287 mg AGE / L of extract with an intense purple color. The validated model showed that the components in the mixture influence in a linear way, the sensory response being less as the extract increases in the formulations. The selected formulation was obtained for 24.1% extract and 60.9% invert syrup, estimating an alcoholic degree of 27.6% (v / v) and 42.6 0Brix, therefore it is classified as a liquor cream according to Cuban regulations. The formulation of cocktails evaluated demonstrated the feasibility of using liquor in traditional cocktails. A classification of “I like it a lot” was obtained for the variant made of the “Creole Daiquiri”.